PENYIMPANGAN SOSIAL MUNITAS MAHASISWA PAPUA DI DENPASAR ( Studi Kasus Konsumsi Minuman Beralkohol ) - Wetipo, Jekson; Ranteallo, Ikma Citra; Tamim, Imron Hadi (JURNAL ILMIAH SOSIOLOGI (SOROT), 2015)
ABSTRACT Deviations consume liquor in the community, students. Data analysis shows that is why they consume liquor, because there are several factors that cause and occurrence forms due to liquor as well as the social impact of irregularities liquor, because they interact in the wider community in the city of Denpasar. According to Durkheim conditions that encourage individualistic nature, social structure and Merton disagreement about the five types of social deviation behaviors of individual adaptation. This research was conducted in July to September 2014 in, in-depth interviews, observation and document study and data analysis. Mechanical determination informant 25 people as key informants. Students Papua alcohol originated from Papua call themselves friends, peers, curiosity, alcohol addiction, self-control is weak, and lack of morals or religion. After alcohol occurs forms and effects of social aberrations, such as sick, accident, theft, fights and pregnancy. Keywords: Irregularities, Consumption of Alcoholic Beverages